Fatigue Life Prediction of Lower Suspension Arm Using Strain-Life Approach - M. M., Rahman; M. M., Noor; K., Kadirgama; M. R. M., Rejab; S. A., Kesulai (© EuroJournals Publishing, Inc., 2009)
This paper presents the fatigue life behaviour of lower suspension arm using strainlife approach. The main objectives of this study are to predict the fatigue life and identify the critical location and to select the suitable materials for the suspension arm. Aluminum alloys are selected as a suspension arm materials. The fatigue life predicted utilizing the finite element based fatigue analysis code. The structural model of the suspension arm was utilizing the Solid works. The finite element model and analysis were performed utilizing the finite element analysis code. In addition, the fatigue life was predicted using the strainlife approach subjected to variable amplitude loading. The three types of variable amplitude are considered in this study. TET10 mesh and maximum principal stress were considered in the linear static stress analysis and the critical location was considered at node (6017). From the fatigue analysis, Smith-Watson-Topper mean stress correction was conservative method when subjected to SAETRN loading, while Coffin-Manson model is applicable when subjected to SAESUS and SAEBRKT loading. From the material optimization, 7075- T6 aluminum alloy is suitable material of the suspension arm. Fatigue Life Prediction of Lower Suspension Arm Using Strain-Life Approach